(untitled) (Hackensack, N.J., 2005)
This volume includes papers by leading mathematicians in the fields of stochastic analysis, white noise theory and quantum information, together with their applications. The papers selected were presented at the International Conference on Stochastic Analysis: Classical and Quantum held at Meijo University, Nagoya, Japan from 1 to 5 November 2004. The large range of subjects covers the latest research in probability theory.
Keywords: Stochastic processes,White noise theory,Quá trình ngẫu nhiên,Lý thuyết nhiễu trắng